Nutzungsanreize und -hemmnisse innovativer multimodaler Kooperationsmodelle im Personenfernverkehr anhand des Fallbeispiels Night&Flight. - Sauter-Servaes, Thomas (My University, 2007)
Verkehrsträgerübergreifende Kooperationen bilden ein interessantes Marketingfeld für den Schienenverkehr im Segment des Personenfernverkehrs. Die Arbeit schildert die gemeinsam von Luft- und Schienenverkehr realisierten intermodalen Verkehrsdienstleistungen. Als innovative Ergänzung werden multimodale Kombimodelle vorgestellt, deren Implementierung und Betrieb bedeutend einfacher und kostengünstiger umzusetzen sind. Pionier im Feld dieser "soft alliances" ist das detailliert betrachtete Fallbeispiel Night&Flight, bei dem eine Nachtzugfahrt und ein One-way-Flug zu einem flexiblen Mobilitätsangebot verknüpft werden. Dieses wird von den Anbietern speziell als Verkehrsdienstleistung für die Zielgruppe Geschäftsreisende beworben. Die Analyse des Geschäftsreisemarktes zeigt auf, dass sich die Verkehrsmittelwahl in den Bereichen Akteure, Kostensensibilität und Finanzierung deutlich von der Privatreise unterscheidet. Gleichzeitig resultieren aus dem wachsenden Kostendruck bei Geschäftsreisebuchungen zwei gegenläufige Trends. Beide durchbrechen die bisherigen Reisebuchungsroutinen und steigern prinzipiell die Markttransparenz, womit die Chance für innovative Angebote wie Night&Flight grundsätzlich steigt. Die Arbeit überprüft, inwieweit das Angebot von der Zielgruppe wahrgenommen wird und wie die theoretischen Nutzenvorteile realisiert werden können. Langfristig ist der nächste Schritt auf der Entwicklungs- und Professionalisierungstreppe "nutzerorganisiert - betreiberorganisiert - providerorganisiert" notwendig, um multimodale Reisen aus dem vollständigen Marktangebot zu erstellen. Eine Softwarelösung muss auf den luftverkehrsseitig bestehenden intramodalen Vergleichswerkzeugen aufbauen und um die Bahnwelt erweitert werden.

Multimodal cooperation is a potentially attractive marketing activity for transport companies offering long-distance passenger service. This research presents results of a case study on an innovative multimodal transport service called Night&Flight implemented by the railway company CityNightLine and Swiss International Airlines. This product was oriented towards business travelers and enabled passengers to take a night train to their destination and a one-way flight on the return journey (or vice versa). By offering a single multimodal product, the Night&Flight program is a pioneer in the field of so-called soft alliances. On the theoretical level many customer advantages can be identified for the Night&Flight product compared to single-mode transport options including temporal flexibility, reliability, and classical soft transport choice factors (novelty, travel time usability, lifestyle). Travel research reveals that the transport mode choice process for business trips differs significantly from that for private journeys in the terms of the actor attributes (decision-making process, access to information), cost sensitivity and financing, however there is increasing pressure to reduce costs in the business travel market. This cost pressure has caused a change in the business travel reservation routine and has increased transparency in the market. Both these trends should, in principle, increase the potential for successfully implementing innovative offers like Night&Fly. In this research, Rogers modified innovation-decision model was used to examine to what extend the Night&Flight service offer was noticed by the target group and which of the service s theoretical advantages were actually valued by customers. The project conducted separate surveys of Night&Flight customers and non-customers. These surveys revealed that night trains cannot acquire new customers by implementing the Night&Flight program; however, current night train-travelers could be enticed to use night trains more often with the Night&Flight program. In addition to the case study, the research presents several different multimodal combination models. The research finds that it will be necessary for transport operators to provide integrated multimodal products to attract business travelers, rather than expecting the customers to create multimodal trips on their own. One potential tool in developing these integrated products involves creating software, similar to airline reservation systems, that includes both airline and railway products. Only by integrating all rail passenger transport services into the system will it be possible to reach the critical mass needed to amortize the high cost of implementing such a system. When developing such a system for multimodal long distance transport, it is critical that the system provide a fair comparison between carrier-specific product characteristics (time, price).
Implementing innovative multimodal cooperation programs in long-distance passenger transport, incentives and barriers identified in the Night&Flight case study.
Keywords: Verkehr; Personenfernverkehr; Eisenbahn; Schienenpersonenverkehr; Verkehrsmittelwahl; Luftverkehrsmittel; Gebrochener Verkehr; Kooperation; Marketing; Verkehrsangebot; Reisekette; Fallbeispiel; Zielgruppe